PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PADA PT. PUSTAKA BENUA PERIODE 2015 - 2019 - DINA ROSMANELIANA (JURNAL ILMIAH KOHESI, 2021)
The purpose of this research is to find out or analyze the influence of company size, profitability and liquidity on capitalstructure in PT. Continental Library. The object of this research on PT. Continental Library located at Jalan BandungNo.24/33, Medan. The type of research used is descriptive quantitative research using secondary data derived from financialstatements from 2015-2019. Data analysis techniques use classic assumption tests, multiple linear regression andhypothesis tests. The results of the study partially showed that the size of the company has no effect on the capital structurewhile profitability and liquidity have a significant effect on the capital structure. Simultaneously shows the size of thecompany, profitability and liquidity affect the capital structure of PT. Continental Library. Adjusted R Square value of 55.4%indicates the ability of the company's size variable (X1), profitability (X2) and liquidity (X3) to affect the capital structure of PTPustaka Benua while the remaining 44.6% is the influence of other free variables that are not explained or not researched byresearchers in this study such as company growth variables, asset structure and business risk.